On uniqueness of equilibrium for complete markets with infinitely many goods and in finance models - Accinelli, Elvio (Estudios de Economía, 2016)
Our concern in this paper is to obtain conditions for the uniqueness of equilibria, with, commodity bundles as consumption patterns which depend on the state of the world. In the first section we consider an economy with complete markets, where consumption spaces are a finite product of measurable function spaces, with separable and proper utility functions and with strictly positive endowments. Using the excess utility function the infinite dimensional problem stated above is reduced to a finite dimensional one. We obtain local uniqueness. The degree theory, and specially the Poincaré-Hopf theorem applied to this excess utility function, allow us to characterize the cardinality of the equilibrium set, and we find conditions for the global uniqueness of this set. On the other hand, we obtain conditions for the uniqueness in economies with incomplete markets and only one good available in each state of the world. When markets are incomplete, equilibrium allocations are typically not Pareto efficient.